Benefits of Implementing a Clustered Oracle Database on Critical Services of the Information Technology - Riccio-Chávez, Francisco Martín (2015)
This scientific article provides a general knowledge about the infrastructure of a clustering Oracle databases, which highlights the primary benefits for companies that offer critical services within the information technology (IT) realm, via a justifi ed investment. For a better understanding, the makeup of this technology will be explained. Various research examples and implementations will also be illustrated, on-premises and off -premises, by the students of the university. It should be noted that this research will be focused on the Oracle Real Application Cluster (RAC) and Oracle Flex Cluster. The fi nal subject is a new feature that provides the Oracle database, which references 12c version technology, with the current date being the same date this article was written.